Death and Honor - Griffin, W. E. B.; Butterworth, William E. (New York : G.P. Putnam's Sons, 2008)
The year is 1943, and Argentina is officially neutral, but crawling with every kind of spy, sympathizer, and military official imaginable. The hero is Cletus Frade, a Marine pilot recruited by the OSS, with strong family ties to Argentina, and a lot on his hands. OSS chief Wild Bill Donovan has asked him to set up his own official-but-really-OSS airline in Argentina, using "loaned" Lockheed Lodestars and Constellations. Of even more concern are two interwoven German operations: a government scheme for Jews outside the Fatherland to purchase the freedom of their relatives in concentration camps, who will then be transported to Argentina and Uruguay; and a plan called Operation Phoenix.
Keywords: United States. -- Marine Corps -- History -- World War II; World War, 1939-1945; Historical fiction; War stories